RECONSTRUCTION OF THE ROLE OF THE GOVERNMENT OF THE DISTRICT OF KOTA IN HANDLING OF PROVINCIAL ROAD LAYING PROGRESSIVE LEGAL - edy praptono (UNISSULA, 2017)
The success of development in a country, strongly influenced by the role of transportation. Development of transportation is very important to support and drive the dynamics of development, because its function as a catalyst in supporting economic growth and regional development. The current condition of Indonesia's transport infrastructure has greatly declined. Damage occurs, especially in provincial roads, so it is necessary to develop transportation infrastructure by the district/city government.